Satisfaction level of sheep and cattle farmeres towards the agricultural extension service in holy karbala province - Al -Darb, Amar Abd Alhassan Ali; AL-Taiy, Hussain K. (Journal of Kerbala for Agricultural Sciences, 2014)
The research aims to identify the level of satisfaction for sheep and cows breeders extension service provided to them was prepared to be a measure of satisfaction of paragraph 36 were distributed among eight axes 1. Goals guidance interest of the breeders and contact with them 2. Topics Extension Service 3. Method of service extension 4. The timing of the extension service 5. Based Service Extension 6. Follow-up 7. The results achieved from the service extension 8stwp of better service extension. Collected data from a random sample of educators participating in extension activities and reached the amount of 98 (72 breeders sheep and 26 breeders cows) mediated questionnaire prepared for this purpose included five satisfaction phrases (strongly satisfied, satisfied, hesitant, not satisfied, not strongly satisfied) and in a manner personal interview. The research found that 67% of surveyed breeders described service Satisfaction level guidance provided to them that he is weak, and in terms of the level of satisfaction with the subject of the extension service provided to them it appeared that 69% -65% of the researchers were their level of satisfaction for each of these subject weak. The researcher recommended to the importance of the formation of the organization of specialized guide for livestock, and the preparation and implementation of a project or program guide specialist with a non-control and evaluation following up, and the importance of thinking in the administration to work indicative. With the need to set up a database on the activity of animal breeding and staff